Forecast of epizootic situation on main helmintosis in Russian Federation for the year 2014 - V. V. Gorohov (Российский паразитологический журнал, 2016)
Observance of epizootic situation in Russian Federation within 1990-2014 in relation to main helminthosis in animals enable to make a conclusion that epizootic process of helminthosis is affected by ecological components: condition of pas- tures, water basins, weather and climate, especially in current pasture season, there- fore it is necessary to carry out antiparasitic treatment.